Base-promoted regioselective synthesis of 1, 2, 3, 4-terahydroquinolines and quinolines from N-boc-3-piperidone. Issue 48 (29th November 2019) - Shally; Althagafi, Ismail; Singhal, Divya; Panwar, Rahul; Shaw, Ranjay; Elagamy, Amr; Pratap, Ramendra
Abstract: An efficient synthesis of 1, 2, 3, 4-tetrahydroquinolines with donor and acceptor group has been delineated by base mediated ring transformation of 6-aryl-4-substituted-2 H -pyran-2-one-3-carbonitriles by N-boc-3-piperidone followed by consecutive deprotection of Boc group under acidic conditions. This reaction involves 2 new bond formations namely C4a-C5 and C8a-C8 in order to create the nucleus. Various donor and acceptor functional groups like aryl, heteroaryl, nitrile, methylsulfanyl and secondary amine were installed in 1, 2, 3, 4-tetrahydroquinolines. We extended our approach to synthesize the fused 1, 2, 3, 4-tetrahydroquinolines by using 2-oxobenzo[ h ]chromenes as precursor. Further, we synthesized fused and isolated quinolines through aromatization of 1, 2, 3, 4-tetrahydroquinolines by DDQ in excellent yields. Single-crystal X-ray analysis of the Boc protected tetrahydroisoquinoline 6t showed the steric hindrance between N-Boc and aryl group. Graphical abstract: Image 1